2012
DOI: 10.4103/0259-1162.103373
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low doses of intrathecal bupivacaine in combined spinal epidural anaesthesia with epidural volume extension for caesarean delivery

Abstract: Aims and Objectives:This study aims to compare relative efficacy of three different doses of intrathecal bupivacaine in combined spinal epidural anaesthesia (CSEA) for caesarean delivery.Materials and Methods:In a double blinded manner, 204 cases were randomized into three groups: I, II, and III to receive a dose of 4, 5.5, and 7 mg of hyperbaric bupivacaine with a fixed dose of 25 μg fentanyl intrathecally, and Dextran 40 w/v 10 mL given for epidural volume extension (EVE), in CSEA. Our primary outcome was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These findings are also supported by a similar study conducted with colloid preload demonstrating an 18% incidence of hypotension under low dose spinal anesthesia (9 mg). [ 2 ] However, our previous study showed a 17.4% incidence of hypotension under the similar spinal anesthetic doses (5.5 mg). [ 3 ] Higher incidence of hypotension in that the study could be accredited to use of crystalloid preload or due to higher sympathetic blockade (sensory block: T2-T3 level) as an effect of epidural volume extension.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These findings are also supported by a similar study conducted with colloid preload demonstrating an 18% incidence of hypotension under low dose spinal anesthesia (9 mg). [ 2 ] However, our previous study showed a 17.4% incidence of hypotension under the similar spinal anesthetic doses (5.5 mg). [ 3 ] Higher incidence of hypotension in that the study could be accredited to use of crystalloid preload or due to higher sympathetic blockade (sensory block: T2-T3 level) as an effect of epidural volume extension.…”
Section: Discussionmentioning
confidence: 92%
“…[ 7 8 9 10 ] We chose a dose of 5.5 mg hyperbaric bupivacaine, considering its safety and efficacy in reduction of hypotension and low failure rates (5%) for cesarean delivery under spinal anesthesia. [ 2 ] With regard to colloid of choice, we opted for Hydroxyl ethyl starch (6%), considering its wider margin of safety against venous thrombosis and allergic reactions. [ 11 ] It is also considered to be safe for the neonate and placental transfer has been found to be negligible even at a 10% concentration in various experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uterine blood flow is not autoregulated, so the uteroplacental perfusion is directly related to maternal blood pressure. 11 Hence, maternal blood pressure can be tolerated only by the mother but not by the fetus. One strategy to maintain both stable hemodynamics and adequate anesthesia block during spinal anesthesia in CS surgery is to use low-dose bupivacaine combined with opioid adjuvant.…”
Section: Discussionmentioning
confidence: 99%